Culture shock (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Annotation: This article explores the phenomenon of culture shock, its stages, coping strategies, and tips for thriving in diverse cultural environments. It provides valuable insights for individuals undergoing cultural transitions, emphasizing the importance of cultural awareness, open-mindedness, seeking support, self-care, and resilience. Additionally, the article highlights the transformative potential of culture shock as an opportunity for personal growth and intercultural competence